Development of Test Instruments for Mathematical Problem-Solving Ability in Algebra Content - Mufidah, Aghniya Syakira; Maimunah, Maimunah; Kartini, Kartini (Suska Journal of mathematics Education, 2025)
Mathematical problem-solving ability (MPSA) is an important competence that supports the development of higher-order thinking skills. However, research shows that students’ MPSA remains low, partly due to the lack of valid and reliable test instruments. This study aims to develop a MPSA test instrument in the form of essay questions on the content of algebraic forms, equations, and linear inequalities in one variable for seventh-grade students at SMP Negeri 13 Pekanbaru. The method used is development research with the Tessmer model, covering the preliminary and formative evaluation stages. The preliminary results indicate that mathematics learning in schools remains dominated by routine, result-oriented questions, while MPSA practice remains limited. Curriculum analysis indicates that the content of phase D algebra requires solving contextual problems, so the instrument was designed to measure the ability to understand problems, plan strategies, solve them, and interpret answers. The design phase produced Prototype I, consisting of 16 essay questions based on MPSA indicators and everyday contexts. Formative evaluation included self-evaluation, expert review, one-to-one, small group, and field tests. Self-evaluation and expert review showed that the instrument was highly valid (average score: 86.20%), with revisions to language, wording, illustrations, and instructions. One-to-one and small group tests produced Prototype II, which was then refined into Prototype III. Field testing with 37 students showed that 15 of 16 items were valid and reliable (coefficient 0.91 for package I; 0.85 for package II) and had good difficulty and discrimination levels, while one item was removed. Thus, the developed instrument is valid, reliable, and feasible for measuring students’ mathematical problem-solving ability.